2012
DOI: 10.1111/j.1463-1318.2011.02918.x
|View full text |Cite
|
Sign up to set email alerts
|

Is whole colonic imaging necessary for symptoms of change in bowel habit and/or rectal bleeding?

Abstract: Twelve patients who had left-sided polyposis and one patient with a strong family history would have undergone whole colonic imaging based on current colorectal cancer management guidelines. The remaining seven patients with right-sided cancer would have been missed if FS were the only investigation used. Patients presenting on the 2ww with symptoms of a CIBH and/or RB can be adequately investigated with a FS with a 3% chance of missing a proximal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…28 It has been suggested that there is scope within the NHS to reduce the diagnostic burden for patients and endoscopy services by implementing clinical protocols which incorporate the selective use of FS, in place of WCI, for the initial investigation of patients with symptoms suggestive of distal CRC. [29][30][31][32][33] For WCI to be avoided in favour of FS, diagnostic protocols using FS for first-line investigation must be able to demonstrate INTRODUCTION NIHR Journals Library www.journalslibrary.nihr.ac.uk favourable risk-benefit profiles, in which the benefits of this less invasive procedure are balanced against the risk of a missed diagnosis of proximal cancer. [34][35][36] The use of such protocols is likely to be most relevant in clinical practice for which the clinical index of suspicion for proximal colon cancer is low, for example when patient and symptom profiles favour a diagnosis of distal CRC.…”
Section: Computerised Tomography Colonographymentioning
confidence: 99%
See 4 more Smart Citations
“…28 It has been suggested that there is scope within the NHS to reduce the diagnostic burden for patients and endoscopy services by implementing clinical protocols which incorporate the selective use of FS, in place of WCI, for the initial investigation of patients with symptoms suggestive of distal CRC. [29][30][31][32][33] For WCI to be avoided in favour of FS, diagnostic protocols using FS for first-line investigation must be able to demonstrate INTRODUCTION NIHR Journals Library www.journalslibrary.nihr.ac.uk favourable risk-benefit profiles, in which the benefits of this less invasive procedure are balanced against the risk of a missed diagnosis of proximal cancer. [34][35][36] The use of such protocols is likely to be most relevant in clinical practice for which the clinical index of suspicion for proximal colon cancer is low, for example when patient and symptom profiles favour a diagnosis of distal CRC.…”
Section: Computerised Tomography Colonographymentioning
confidence: 99%
“…37,[53][54][55][56][57] The sensitivity of rectal bleeding for proximal lesions has been shown to be higher in elderly patients (those aged ≥ 80 years) 58 or when bleeding is severe. 54 A CIBH with rectal bleeding is also associated with distal CRC, 29 but it is less clear whether or not a CIBH without rectal bleeding can be used to distinguish distal from proximal CRC. 35 Symptoms and signs suggestive of proximal colon cancer Cancers in the proximal colon are, in general, less likely to present with overt symptoms such as rectal bleeding.…”
Section: Symptoms Suggestive Of Distal Colorectal Cancermentioning
confidence: 99%
See 3 more Smart Citations